Predictors of willingness to support and engage in nonviolent civil disobedience to defend the climate - Patrick O. Ansah; Nicholas Badullovich; Teresa Myers; John Kotcher; Seth A. Rosenthal; Anthony Leiserowitz; Edward Maibach (npj Climate Action)
Abstract Some climate activists use nonviolent civil disobedience (NVCD) to protest the slow pace of climate policy action. Civil disobedience theorists posit that building a critical mass of support for and participation in NVCD increases the likelihood of policy success. Here we investigate predictors of public support for and personal willingness to engage in NVCD using data from a nationally representative survey of U.S. adults (n = 1303). Linear regression analysis revealed the following significant predictors of public willingness to support and engage in NVCD: collective efficacy; anger; identification with climate activists; descriptive norms and exposure to liberal news media. Similarly, all these variables were significant in the relative weight analysis. These findings provide theoretical and practical insights into the role of NVCD in the climate movement.